La medición en el proceso de investigación científica: Evaluación de validez de contenido y confiabilidad (Measurement in the scientific research process: Content validity and reliability evaluation) - Mendoza Mendoza, J. G.; Garza, J. B. (Facultad de Contaduría Pública y Administración U.A.N.L., 2009)
Abstract. In scientific research a relevant issue is measurement. Elements that form part of the measurement process are discussed. These elements are the following: the operationalization of variables, the relationship among theory and measurement, scales as measurement instruments, the meaning of the latent variable, validity and reliability as essential properties of measurement, also including content validity. Through the understanding of these elements, the relevance of the measurement process is established. Besides, the process of content validity and the estimation of reliability of a developed scale are described.